The Roles of English Teacher Forum (MGMP) in Indonesia Towards the Teacher Professional Development - Septian Hanung Dwi Atmoko; Paulus Kuswandono (Yayasan Visi Intan Permata, 2021)
This research was conducted to look for the roles of the English teacher forum (MGMP) in Klaten, Central Java, Indonesia as an integral part of their teacher professional development (TPD). The abbreviation of MGMP stands for Musyawarah Guru Mata Pelajaran or English Teacher Forum in the context of this study. The research involved fifteen English teachers from various accessible schools. The phenomenological method was used in this research to understand the teachers’ experiences of the contribution of MGMP towards their TPD. Further, the research utilized a questionnaire and interviews to collect the data from the participants. The three-step data analysis from Ary, Jacsobs, Sorensen, & Razavieh (2010) namely familiarizing and organizing, coding and reducing, and interpreting and representing were employed to validate the data. The results demonstrate that MGMP gives a lot of benefits to the TPD. Nevertheless, some aspects should be improved, such as conducting research on teachers’ training needs, providing sustainable post-training supervision, and creating simple and efficient systems related to the school administration. For future research direction, further studies should focus on improving those aforementioned factors.